PEMIKIRAN FIKIH SOSIAL KH. SAHAL MAHFUDH DAN DAN KH. ALI YAFIE TENTANG RELASI MAYORITAS-MINORITAS DI INDONESIA - Siddiq, Akhmad (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
Plurality creates friction which there are two poles; majority and minority. Relation both do not always go hand in hand, and often reaches the tension which, strangely, is supported by the legitimacy of the Islamic law itself. So, we need jurisprudence that offers contextualization, accommodating, flexible and prioritize the benefit principle. This jurisprudence models get touch of two charismatic of NU, namely KH. Sahal Mahfudh and KH. Ali Yafie. KH. Sahal Mahfudh reconstruction of mazhab’s patterns and make improvements to the existing jurisprudence concept. While KH. Ali Yafie interpreting verses of the Koran directly by incorporating sociological aspects into consideration. KH. Sahal Mahfudh’s approach emphasized maslahah mursalah and Ali Yafie which rests on the analysis of concrete implications kifayah obligatory on the ideal of majority-minority relations in Indonesia. According to both, the relation whatever to uphold human values are summarized in the maqasid al-Shari’ah. There is no reason to feuding let alone each other down though clearly different religion, and ideology. Friction friction happens to be completed if supported by an intense dialogue. This, according to Sahl Mahfudh a boarding duties and responsibilities. At this point, social jurisprudence exists as a social ethics guidelines that are not partial.